A New Compact and Wide-band Band-stop Filter Using Rectangular SRR - B. Nasiri; A. Errkik; J. Zbitou; A. Tajmouati; L. El Abdellaoui; M. Latrach (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
This paper proposes a novel compact band-stop filter based on Rectangular SRR unit cell. The BSF structure consists of modified microstrip line connected to 50 Ω feed line on both sides and Rectangular-SRR which has been added and located in the center of the proposed design. The R-SRR dimensions are chosen and optimized in order to achieve a resonant frequency in the undesired band. This filter is designed, simulated and optimized using two electromagnetic solvers. The circuit performances have been investigated and found to have an excellent BSF characterized by high power rejection level in the stop-band, low insertion loss in the both pass-bands and compact size. The experimental results illustrate that the proposed BSF achieves a wide fractional bandwidth of 72 % at 2.2GHz.